MacSween's pathology of the liver - Burt, Alastair D.; Portman, Bernard C.; Ferrell, Linda D.; MacSween, Roderick N.M (Churchill Livingstone Elsevier, 2007)
Revised and thoroughly updated fifth edition provides all of the information necessary to effectively diagnose and confidently sign out hepatobilary tissue samples. An invaluable aid to pathologists at all levels of training and practice, this book covers the full range of both benign and malignant lesions of the liver and biliary tract. All entities are accompanied by carefully chosen photographs of outstanding quality. Summary tables, diagnostic flow charts, and analytic tables give the information needed for rapid interpretation and accurate diagnosis.